The Montreal Criteria and uterine transplants in transgender women - Balayla, Jacques (Bioethics, 2021)
Ever since its first documented live birth in 2014, the use of uterine transplantation (UTx) for the treatment of absolute uterine factor infertility (UFI) has seen major clinical advances, which include the use of alternative surgical approaches, different donor states, and diverse patient populations. In addition to the thorough research programs that developed the technique, this accomplishment has occurred in large part following a number of ethical frameworks, such as the Montreal Criteria and the Indianapolis Consensus, which paved the way to transition from experimental animal trials to human ones. To date, over 60 uterine transplants have been performed in the world, and at least 18 births have been thus far confirmed. While the procedure remains experimental, the vast knowledge and procedural experience amassed over the last 20 years of rigorous research have hinted at the next step of discovery. In particular, advancing social circumstances have prompted the question regarding the use of this technology in transgender individuals. Though the potential use of uterine transplants in the transgender population has been hypothesized, no in-depth ethical framework has been developed towards this purpose. Herein, we explore the ethical issues revolving around the use of this technology in this patient population and provide key insights that may advance this cause.